Mosquito control activities associated with dengue hemorrhagic fever in Indonesia: A literature review - Puspita, Yashinta Dwi; Sulistiyani, Sulistiyani; Darundiati, Yusniar Hanani; Dewanti, Nikie Astorina Yunita (Faculty of Medicine, Universitas Islam Indonesia, 2024)
Dengue Hemorrhagic Fever (DHF) is an endemic disease. It has become a public health concern. Mosquito control activities are needed to control vectors and prevent DHF. Therefore, we conduct a literature review of mosquito control activities associated with DHF in Indonesia. This study applies the selected articles using PRISMA (Preferred reporting items for systematic reviews and meta-analyses), and they are sourced from Science Direct, Google Scholar, Scopus, ProQuest, Ebscohost, and Portal Garuda. The criteria for the selected articles are full-text articles, published in 2015-2020, and those which are published in national journals SINTA 2 or international journals. This study reviewed 683 articles, out of which were selected for further examination. The key variables, such as draining water containers, covering water containers, burying and recycling used containers, using mosquito repellent, using larvacide , keeping larva-eating fish, having mosquito repellent plants, installing wire mesh on ventilation, showed significant correlation with Dengue Hemorrhagic Fever (DHF) incidence. Among the selected articles, 38.89% employed cross-sectional design, and the rest belonged to case-control studies. Most articles have variable draining water containers (55.56%), 50% covers water containers, 80% have a significant association between draining water containers and DHF incidence, and 66.67% have a significant association between covering water containers and DHF incidence. Most articles show that not implementing PSN (Pemberantasan sarang nyamuk) or PSN 3M (Pemberantasan sarang nyamuk, menguras, menutup, mengubur plus) is associated with the incidence of DHF and is a risk factor for the occurrence of DHF. On the other hand, the implementation of PSN or PSN 3M Plus will be a protective factor.